Syk and ZAP-70 mediate recruitment of p56lck/CD4 to the activated T cell receptor/CD3/zeta complex. - Thome, M; Duplay, P; Guttinger, M; Acuto, O (1995)
During antigen recognition by T cells, CD4 and the T-cell receptor (TCR)/CD3/zeta complex are thought to interact with the same major histocompatibility complex II molecule in a stable ternary complex. Evidence has suggested that the association of CD4 with TCR/CD3/zeta requires the interaction of the protein tyrosine kinase p56lck with CD4. We have taken a biochemical approach to understand the mechanism by which p56lck and, in particular, its src homology (SH) 2 domain contributes to the association of CD4 with TCR/CD3/zeta during activation. We have previously shown that the p56lck SH2 domain binds directly to tyrosine-phosphorylated ZAP-70. Here we formally demonstrate the in vivo association of p56lck with the homologous protein tyrosine kinases Syk and ZAP-70 after CD3 stimulation of Jurkat cells. A tyrosine-phosphorylated peptide containing the sequence predicted to be optimal for binding to the SH2 domain of src family kinases specifically competes for this association, indicating that tyrosine-phosphorylated ZAP-70 and Syk bind to p56lck by an SH2-mediated interaction. We also show that the same peptide is able to compete for the activation-dependent TCR/CD4 association in Jurkat cells. Moreover, ZAP-70 and CD4 cocap only after CD3 stimulation in human T lymphoblasts. We propose that the interaction of the p56lck SH2 domain with zeta-associated tyrosine-phosphorylated ZAP-70 and/or Syk enables CD4 to associate with antigen-stimulated TCR/CD3/zeta complexes.